Assessment of Hemodynamic Effects of Etomidate versus Propofol in Elective Surgical Patients - A Clinical Study - Lokesh Kumar Gupta; Keshav Dev Jagar (Academia Anesthesiologica International, 2020)
Background: Hemodynamic stability during laryngoscopy and intubation with minimal side effects is the main objective of any anaesthetist. The present study was conducted to assess hemodynamic effects of etomidate versus propofol in elective surgical patients. Subjects and Methods: The present study was conducted on 48 patients planned for elective surgery of both genders. Patients were divided into 2 groups of 24 each. Group I patients were given propofol (P) and group II were given the etomidate. Parameters were recorded. Results: The mean height in group I patients was 165.2 cm and in group II was 166.7 cm, mean weight was 68.1 kg in group I and 65.2 kg in group II. Mean MAP (mm Hg) at T1 in group I was 118, T2 was 90, T3 was 102 and T4 was 106. In group II, T1 was 110, T2 was 94, T3 was 98 and T4 was 100. The difference was non- significant (P> 0.05). Mean HR (beats/min) at T1 in group I was 77.2, T2 was 79.4, T3 was 81.5 and T4 was 79.1. In group II at T1 was 75.4, T2 was 81.6, at T3 was 87.2 and at T4 was 84.3. No statistical significance was observed in between both the groups on comparing Heart Rate and Mean Arterial Pressure. Conclusion: Both Etomidate and Propofol are equally effective in terms of their hemodynamic effects.